(untitled) (Eurasian Journal of Philology Science and Education, 2022)
Тhe article is devoted to the study of pragmatic acts of political communication. In this article, the authors consider the phono-stylistic features, and also explore the communicative-pragmatic structure of the act of threatening speech. Researchers are interested in studying the impact of the verbal use of political figures on the social environment, acts of intimidation, aggression and aggressive speech. Modern linguistics is a collection of different areas of research, the leading of which at this stage are two – pragmatic ones related to the functional properties of language, that is, the conceptualization of the cognitive world, which studies the relationship of language to a communication partner and the role of language and consciousness in categorization, cognitive processes and generalization of human experience, the relationship of individual cognitive abilities of a person with language and the forms of their interaction. The illocutionary acts used by a person in daily communication are the same sound symbols as words. They have their own differential intonation features, on the basis of which they are recognized in the process of interaction and which determine the forms of response of communication partners. The process of speech interaction of people is based on this. As a result of the study, we found that the true intonation of the speaker, the tone of speech in sound form, gestures and facial expressions, as well as the motives, goals, interests of the politician, the results of speech activity can be accurately predicted